Appropriateness and Effectiveness of Spanking : a Study of Child Misbehavior and Child-Adult Relationship - Lukes, Anna L.; Poncelet, Tara L. (My University, 2011)
Two types of misbehavior are common among children. Aggressive behavior is defined as either hitting or kicking, whereas passive misbehavior is defined as disobeying or talking back to an adult. Adults should apply disciplinary actions to subdue the misbehavior; however, the perceptions of different forms of discipline can be influenced by the child-adult relationship (either child-parent or child-babysitter). This study explores the appropriateness and effectiveness of spanking as a form of child discipline.
Color poster with text and graphs.
Keywords: Discipline of children--Psychological aspects; Children--Conduct of life; Parent and child--Research; Babysitters--Statistics; Posters